Person-centered medicine: a call to the origin - Vargas Vargas, Jeimy Lorena (Subcomité editorial y de evaluación de obras de la Facultad de Ciencias de la Salud Editora Revista Dra. Bibiana Matilde Bernal Gómez, 2022)
Traditionally, medicine has been reconciled with the science and art of caring for women, as there are many classic authors who address issues such as ethics and morals in medical professionals; Specifically, as part of the novel culture, the full and honorable dedication of medical practice to its patient arises, without shame, doctors who live in deep reflection and sincerity about their actuary and origin of being; It is well known that there are positions regarding the ownership of medicine, the first from the vision of the biomedical model (positivist) and the second from the biopsychosocial vision of centralized care in the person, which has foundations and characteristics that are of different depth ; Finally, it is concluded that if the bases of the biopsychosocial model and in particular the center of attention centered on the person constitutes a way of understanding the reality of the human being, it does not contradict the biomedical model itself that complements it, and finally the paradigm of the Cos school: “the science of serving people”; In this sense, this paper intends to focus on health personnel and in particular on medical personnel in terms of the importance of acting in favor of patients in the clinical and political ambiguity that must be taken only in the individual approach, both in the community and in the public.